Actions, contexts, mechanisms and outcomes in macroprudential policy design and implementation. (April 2021) - Bakir, Caner
Causal mechanisms have received significant attention within the social sciences, and policy design and implementation occupy a prominent place in public policymaking. However, one area that has not received much attention in this literature is the causal mechanisms that are able to link policy instruments with outcomes due to operating within the appropriate contexts. This article seeks to fill this gap in the literature. Drawing on realistic evaluation and comparative historical institutionalism, and an exploratory case study on macroprudential regulation in Turkey between June 2011 and September 2016, this article argues that the success of macroprudential instruments in securing of macrofinancial stability is most likely when they trigger causal mechanisms that operate within the appropriate contexts.